Validity and Intra Rater Reliability of a New Device for Tongue Force Measurement - Diaz-Saez, Marta Carlota; Beltran-Alacreu, Hector; Gil-Castillo, Javier; Navarro-Fernández, Gonzalo; Cebrian Carretero, Jose Luis; Gil-Martínez, Alfonso (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2023)
Background. The tongue is made up of multiple muscles both extrinsic and intrinsic. The hyoid, jaw and maxillary complex contain the tongue, which hangs between these structures forming an important biomechanical system. This organ has to work in coordination with craniofacial structures to ensure normal orofacial functioning. There are different devices on the market for tongue force measurement. However, they are not accessible for patients due to their size and very high prices. Likewise, other devices have not yet carried out validity and reliability studies. The purpose of this study was to validate a new device proving that it is accurate compared to the algometer. Moreover, the study wanted to determine the intra-rater reliability of a protocol to assess the maximum tongue force in asymptomatic subjects. Material and methods. This is an observational-longitudinal study with repeated measurements. A prototype device was developed specifically for this study to measure tongue force through force-sensitive resistor sensors. The prototype system was equipped with a device to perform and transmit the measurement and a C++ programming software in the computer to take data from the session. Different formulas were made to calibrate the system. For validity, the force measured by the prototype and the algometer was compared. For intra-rater reliability, 29 asymptomatic Spanish subjects were recruited, and a standardized protocol was carried out for the tests. Results. Experiments to assess validity showed a strong correlation (r>0.97) and an excellent reliability (ICC>0.90) between devices.On the other hand, the intra-rater reliability analysis showed an excellent ICC (0.93) with a 95% CI of 0.86 to 0.97 and a MDC90 of 6.26N. Conclusion. We demonstrated good validity values and high intra-rater reliability for the prototype device for the maximum tongue force.
Keywords: device; temporomandibular disorders; tongue force; IJIMAI